Nitrogen Application Effects on Forage Sorghum Biomass Production and Nitrates - A. Obour; J. D. Holman; D. B. Mengel (Kansas Agricultural Experiment Station Research Reports, 2018)
Forage sorghum (Sorghum bicolor(L.) Moench) is a highly productive annual summer forage that can be grazed, hayed or ensiled for winter feed, confined feeding, or grazed to supplement native pasture. Recently, there has been interest in growing forage sorghum for hay or grazing in place of fallow to increase residue cover as part of an integrated forage or cover crop system. The high water use efficiency and heat and drought tolerance of sorghum makes it an ideal forage crop choice for growers in the water-limited Great Plains environment. Furthermore, due to the declining saturated thickness of the Ogallala and High Plains aquifers, there is a need for more water efficient forages like sorghum compared to corn silage or alfalfa. Despite the great potential of forage sorghum as animal feed, high nitrate content is a major concern when fed to cattle. Forage containing 3,000 ppm nitrates are generally considered safe as livestock feed, nitrate concentrations between 3,000 and 6,000 ppm may be limit fed, and concentrations>9,000 ppm should not be fed to livestock. Ensiling reduces nitrate concentration but still requires caution when fed. Environmental stressors (including drought, frost, or cloudy weather conditions) and high manure or N fertilizer application rates can predispose forage crops to accumulate greater nitrate concentration in the aboveground biomass. Nitrogen application generally increased DM production, but excessive N application will also increase nitrate concentration in the harvested biomass. Limited research has been conducted on forage sorghum DM production and nitrate concentration responses to N fertilizer application in the semi-arid Great Plains region. Objectives of this study were to determine optimum N rates and quantify forage sorghum hay nitrate concentration as affected by N application under rain-fed no-till conditions in the semiarid central Great Plains.
Keywords: Nitrogen fertilization; nitrogen application; grain sorghum